Advances in the Pharmacology of Lgics Auxiliary Subunits - Barra-Pezo, R (Academic Press, 2015)
Ligand-gated ion channels (LGICs) are cell surface integral proteins that mediate the fast neurotransmission in the nervous system. LGICs require auxiliary subunits for their trafficking, assembly and pharmacological modulation. Auxiliary subunits do not form functional homomeric receptors, but are reported to assemble with the principal subunits in order to modulate their pharmacological profiles. For example, nACh receptors are built at least by co-assemble of α and β subunits, and the neuronal auxiliary subunits β3 and α5 and muscle type β, δ, γ, and ε determine the agonist affinity of these receptors. Serotonergic 5-HT3B, 5-HT3C, 5-HT3D and 5-HT3E are reported to assemble with the 5-HT3A subunit to modulate its pharmacological profile. Functional studies evaluating the role of γ2 and δ auxiliary subunits of GABAA receptors have made important advances in the understanding of the action of benzodiazepines, ethanol and neurosteroids. Glycine receptors are composed principally by α1-3 subunits and the auxiliary subunit β determines their synaptic location and their pharmacological response to propofol and ethanol. NMDA receptors appear to be functional as heterotetrameric channels. So far, the existence of NMDA auxiliary subunits is controversial. On the other hand, Kainate receptors are modulated by NETO 1 and 2. AMPA receptors are modulated by TARPs, Shisa 9, CKAMP44, CNIH2-3 auxiliary proteins reported that controls their trafficking, conductance and gating of channels. P2X receptors are able to associate with auxiliary Pannexin-1 protein to modulate P2X7 receptors. Considering the pharmacological relevance of different LGICs auxiliary subunits in the present work we will highlight the therapeutic potential of these modulator proteins. © 2015 Elsevier Ltd. All rights reserved.